Remote sensing and GIS application for monitoring forest management operations - Ratnayake, Ranitha (2004)
Satellite data potentially provide a useful tool for estimating forest cover and monitoring changes. Traditional forest surveying methods involve time consuming measurements of a large number of trees. Remotely sensed data may enable forest cover changes to be estimated very rapidly over large areas and with a minimum of ground data collection. At present the role of forest management in Britain is expanding, so that looking at forest cover changes is extremely useful for management purposes.